Assessment of Key factors of the foreign Exchange Rate formation in armenia - E. M. Sandoyan; M. A. Voskanyan; A. G. Galstyan (Финансы: теория и практика, 2018)
Usually, it is diffcult for developing countries to choose a currency regulation policy because of institutional inadequacy, including a signifcant level of concentration in commodity markets, and a high degree of dependence of the national market and fnancial system on exogenous factors and a huge external debt. This article is dedicated to the analysis and evaluation of key factors affecting the formation of the Armenian national currency (dram) exchange rate, as well as to the choice of the currency regulation policy in Armenia. The authors carried out a statistical and econometric analysis of the factors of the foreign exchange rate formation, taking into account the specifcs of the transition economy as a whole, as well as the features of the Armenian economy, in particular. The authors have identifed the exogenous and endogenous factors of the foreign exchange rate formation of the dram, depending on the inﬂow and outﬂow of foreign currency. Further, the authors specifed the inﬂuence of dominant factors on the choice of the currency regulation policy in the country. The authors carried out an econometric analysis of the factors identifed at the frst stage of the study using the VAR model. The results obtained from this model proved the hypothesis of the non-market nature of the dram’s exchange rate formation. The authors concluded that the dram’s exchange rate formation has non-market nature because of signifcant intervention on the currency market by the “monetary authorities”. The key conclusion of this study is the thesis about the need to change the approaches to currency regulation in Armenia in favour of the transition to a free-ﬂoating exchange rate policy in order to stimulate sustainable rates of economic growth in the long term.